2022
DOI: 10.1371/journal.pone.0265365
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of emission product distribution from vaping of vitamin E acetate

Abstract: Nearly two years after vitamin E acetate (VEA) was identified as the potential cause of the 2019–2020 outbreak of e-cigarette, or vaping product-associated lung injuries (EVALI), the toxicity mechanisms of VEA vaping are still yet to be fully understood. Studies since the outbreak have found that e-liquids such as VEA undergo thermal degradation during the vaping process to produce various degradation products, which may pose a greater risk of toxicity than exposure to unvaped VEA. Additionally, a wide range o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(30 citation statements)
references
References 49 publications
(77 reference statements)
2
25
0
Order By: Relevance
“…Catalysis, viscosity, airflow, device quality, and user behavior can each exacerbate toxicant formation, apart from the temperature settings . Importantly, the study herein validates the findings of Wu and O’Shea as well as others showing that vaping conditions can lead to ketene formation at apparently lower temperature settings than previously assumed. ,,, …”
supporting
confidence: 86%
See 2 more Smart Citations
“…Catalysis, viscosity, airflow, device quality, and user behavior can each exacerbate toxicant formation, apart from the temperature settings . Importantly, the study herein validates the findings of Wu and O’Shea as well as others showing that vaping conditions can lead to ketene formation at apparently lower temperature settings than previously assumed. ,,, …”
supporting
confidence: 86%
“…Therefore, ketene does not survive long enough to be detected intact in vivo . Chemical and physical studies such as reported herein and by others , are thus needed to elucidate sources of exposure.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Recent research has revealed that the inhalation of aerosols released by e-cigarettes has the potential to negatively impact the lungs of users, despite the prevalent assumption of safety among e-cigarette consumers. , Though many commonly used e-liquid ingredients, including propylene glycol (PG), glycerin (VG), and various flavoring agents, are considered safe for consumption or dermal absorption, emitted aerosols are complex mixtures of compounds formed from the thermal degradation of e-liquids that occurs during the vaping process . This process results in the formation of emission products with different physiochemical properties and a risk of toxicity potentially greater than that posed by the parent e-liquids. For example, vitamin E acetate (VEA), the proposed cause of the e-cigarette or vaping-associated lung injury (EVALI) outbreak in the United States in 2019, has been found to decompose into thermal degradation products, including vitamin E (VE), various long-chain alcohols, alkenes, carbonyls, and, most notably, the reactive species duroquinone (DQ) and ketene. ,, While VEA itself is perceived as safe, the inhalation of electrophilic species like DQ produced during vaping poses a serious risk of oxidative damage to lung tissue. , As such, to understand the potential health risk to users, the prediction of the thermal degradation behavior of various e-liquids through computational and experimental methods has been of particular interest in recent e-cigarette research.…”
Section: Introductionmentioning
confidence: 99%
“…In e-cigarette systems, the presence of metal filament wires has been suggested to have strong catalytic effects on the thermal degradation of PG and VG, reducing the temperature needed to observe carbonyl-containing compounds in vaping emissions. , Furthermore, metal catalysis has been found to be an important factor in thermal degradation pathways in analyses of systems such as biochar . The presence of O 2 has also been found to greatly decrease the temperature required to observe the thermal degradation of PG and VG and may play an important role in the low-temperature degradation of e-liquids. ,, …”
Section: Introductionmentioning
confidence: 99%